ANALISIS WILLINGNESS TO PAY PADA WISATA BUKIT MATANG KALADAN DESA TIWINGAN LAMA KECAMATAN ARANIO KABUPATEN BANJAR KALIMANTAN SELATAN - Muhammad Rauhan Fikri; Noor Rahmini (PPJP Universitas Lambung Mangkurat, 2020)
This research was conducted to find out: (1) To analyze the willingness of tourists to pay (Willingness to Pay) in Bukit Matang Kaladan Tourism (2) To find out whether factors of education, income, number of family members and travel costs affect travel value (Willingness to Pay) Bukit Matang Kaladan Tourism. (3) To find out the most dominant factors influencing the willingness of tourists to pay (Willingness to Pay) towards the Bukit Matang Kaladan attraction.The analytical method used is the Willingness to Pay (WTP) and Regression approach with research variables namely education, income, number of family members and travel costs. The data source is primary data obtained through direct interviews with Bukit Matang Kaladan tourists according to criteria using a questionnaire.The results of calculations using the Willingness to Pay (WTP) and Regression Approach method show the average willingness to pay is Rp 11,260. If there is an increase in quality, the average amount that is willing to be added by respondents is Rp. 7,760 so that the average willingness to pay respondents to travel to Bukit Matang Kaladan is Rp. 19,020. Significant variables in this study are education, income and travel cost and the insignificant variable is the number of family members. While the most dominant factor in this study is travel cost.Keywords: Willingness to Pay (WTP), Bukit Matang Kaladan, Travel Costs